SENAM TEPUK SAKINAH SEBAGAI INTERVENSI EDUKATIF DALAM MENINGKATKAN KEHARMONISAN KELUARGA GURU - Yudi Karisma Sari; Muhammad Fajrul Falaah; Rakan Raditya Kurniawan; Cristian Batistuta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study is to determine the effectiveness of Senam Tepuk Sakinah in creating harmony within the families of teachers at SDN Bororejo, Jebres District, Surakarta City. This study was conducted using a quantitative approach and employed a one-group pretest-posttest design. Nine married teachers participated in the Senam Tepuk Sakinah program for four weeks. To obtain quantitative data, the research instrument used a family harmony questionnaire, which includes elements of communication, togetherness, and emotional closeness. In addition, observation sheets were also used. To determine the difference between scores before and after the intervention, data analysis was conducted using descriptive statistics and paired sample t-test. The research results show that performing Senam Tepuk Sakinah increases the family harmony score by 25.5%. This improves family communication, togetherness, and emotional closeness. The statistical test results indicate that Senam Tepuk Sakinah is effective in enhancing family harmony (p < 0.05). Observation results also showed that participants were very enthusiastic, active, and interacted well during the activity. The results show that Senam Tepuk Sakinah can be an alternative educational method that is simple, enjoyable, and easy to implement to build communication and family togetherness, especially for teachers who act as parents and educators in schools.